Age Influences the Prognosis of Anaplastic Thyroid Cancer Patients - Kong, Na; Xu, Qiqi; Zhang, Ziqin; Cui, Aimin; Tan, Shen; Bai, Nan (Frontiers in Endocrinology, 2021)
Background: The staging system for patients with anaplastic thyroid cancer (ATC) was updated in the 8th edition of the American Joint Committee on Cancer Staging manual. A cut-off age of 55 years was stipulated as a prognostic factor for differentiated thyroid cancer; however, age was not considered for ATC patients. To fill this gap, this study investigated the relationship between age at diagnosis and prognosis of ATC patients. Methods: The clinical information on ATC patients was acquired from the Surveillance, Epidemiology, and End Results Program public database. Youden’s index and X-tile analyses were used to calculate the high-point of the age at diagnosis that was associated with prognosis. Cox proportional hazards models, Kaplan-Meier curves, and 1000-person-year were then used for verifying the accuracy of the high-point age. Results: After inclusion/exclusion criteria, 586 patients were included in this study. The high-point age was determined to be 70 years by both the Youden’s index and X-tile plot methodes. The hazard ratio was 1.662 (95% confidence interval [CI]: 1.321-2.092), indicating there was an increased risk of poor prognosis for patients > 70 years of age. The cancer-specific mortality rates per 1000-person-years for patients ≤ and > 70 years-old were 949.980 (95% CI: 827.323-1090.822) and 1546.667 (95% CI: 1333.114-1794.428), respectively. P-values were < 0.001 for the results shown above. Conclusion: Our study found that age influenced the prognosis of ATC patients. Furthermore, we determined that the high-point of age at diagnosis was 70 years and that > 70 years of age was associated with a poor prognosis. These results provide a useful addition to the staging manual and can improve the diagnosis, treatment strategies and prognosis of ATC patients.